1997
DOI: 10.1046/j.1365-2842.1997.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Denture stomatitis in an elderly edentulous Asian population

Abstract: Denture stomatitis is a common oral disease in denture wearers. Multiple aetiological and predisposing factors are believed to be responsible for its initiation and progression. The aim of this study was to assess the relationship between denture age, denture hygiene habits, denture wearing and denture cleanliness in an elderly edentulous Asian population. Seventy-five edentulous patients, all wearing maxillary complete dentures were divided into two groups. The test group comprised 36 patients (14 male and 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
36
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 16 publications
4
36
0
8
Order By: Relevance
“…However, overnight denture-wear was found to be a major risk factor in Jeganathan's study, 14 and this is consistent with the present findings. It is possible that the similarity in the identified DS risk factors is somehow related to the study design.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…However, overnight denture-wear was found to be a major risk factor in Jeganathan's study, 14 and this is consistent with the present findings. It is possible that the similarity in the identified DS risk factors is somehow related to the study design.…”
supporting
confidence: 92%
“…13 Some studies have reported the continuous and round-the-clock wearing of dentures as an aetiological local factor involved in the pathogenesis of DS. 14,15 Poorlyfabricated dentures have a lot of porosities in their acrylic base, which encourages the adhesion of C. albicans, making it difficult to maintain denture hygiene. 1,7 The frequency of dental visits by denturewearing patients each year and the number of years since denture manufacture (denture age) have also been reported as local factors contributing to DS.…”
mentioning
confidence: 99%
See 3 more Smart Citations